A unified trans-scale mechanical properties prediction method of 3D composites with void defects. (15th February 2023) - Huang, Hao; Shan, Zhongde; Liu, Jianhua; Sun, Zheng; Guo, Zitong; Gong, Hao; Xia, Huanxiong; Jin, Peng; Chen, Chaozhong
Abstract: Void defects are inevitable in 3D composites impregnated with resin, making a detrimental effect on the mechanical properties. To predict the mechanical properties of 3D composites with void defects comprehensively and accurately, a unified trans -scale method is developed by integrating experiments, analytical model(ANM) and finite element model(FEM). The trans -scale experiments on fiber tows and 3D orthogonal structures are conducted combining with Micro-CT to provide geometric parameters and longitudinal direction verification for ANM and FEM. To predict all elastic constants, a modified Chamis model on the micro-scale and a stiffness average method on the meso-scale with void defects are proposed. A trans -scale FEM with void defects is established to verify the ANM and investigate the effects of void defects. The results show that the proposed ANM has high agreement with FEM on the micro-scale and meso-scale respectively. The relative errors of ANM and FEM on the micro-scale to the experimental results on longitudinal direction are all less than 1%, which means that both models are accurate and reliable. The void defects in fiber tows have more significant effects on in-plane elastic modulus than that out-of-plane while those in 3D orthogonal structures make a greater influence on shear modulus than tensile modulus.